Role of neoadjuvant chemotherapy in resectable synchronous colorectal liver metastasis; An international multi‐center data analysis using LiverMetSurvey. Issue 6 (9th April 2015) - Bonney, Glenn K.; Coldham, Chris; Adam, Rene; Kaiser, Gernot; Barroso, Eduardo; Capussotti, Lorenzo; Laurent, Christophe; Verhoef, Cees; Nuzzo, Gennaro; Elias, Dominique; Lapointe, Real; Hubert, Catherine; et al.
Abstract: Background and objectives: The use of neo‐adjuvant chemotherapy in resectable synchronous liver metastasis is ill defined. The aim of this study was to evaluate neo‐adjuvant chemotherapy on outcomes following liver resection for synchronous CLM. Methods: An analysis of a multi‐centric cohort from the LiverMetSurvey International Registry, who had undergone curative resections for synchronous CLM was undertaken. Patients who received neo‐adjuvant chemotherapy prior to liver surgery (group NAS; n = 693) were compared with those treated by surgery alone (group SG; n = 608). Baseline clinicopathological variables were compared. Predictors of overall (OS) and disease free survival (DFS) were subsequently identified. Results: Clinicopathological comparison of the groups revealed a greater proportion of solitary metastasis in the SG compared to the NAS group (58.8% versus 38.4%; P  < 0.001) therefore a separate analysis of solitary versus multi‐centric analysis was performed. N‐stage (>N1), number of metastasis (>3), serum CEA (>5ng/ml) and no adjuvant chemotherapy independently predicted poorer OS, while N‐stage (>N1), serum CEA (>5ng/ml) and no adjuvant chemotherapy independently predicted poorer DFS. Neo‐adjuvant chemotherapy did not independently affect outcome. Conclusion: We present an analysis of a large multi‐center series of the role of neo‐adjuvant chemotherapy in resectable CLM and demonstrate no survival advantage in this setting. J. Surg. Oncol. 2015 111:716–724 . © 2015 Wiley Periodicals, Inc.